SOME TRENDS IN REGIONAL DISPARITIES IN PRIMARY SCHOOL PARTICIPATION IN ETHIOPIA - Ayalew, Shibeshi (The Ethiopian Journal of Education, 2024)
Since 197J/74.J vast strides have been made to democratize education and increase regiona l participation rates in primary education . Despite the efforts made however.J dispari ties have widened and widened in a zonal nature.J denoting the geogrdphicaUy distinct areas of i.C pth and south. The factors that underlie the problem seem to be distribution of missionary schools.J economic differences in the regions and lack of stability in some of the wrthern regions. Whereas regional disparities in educational participation are very difficult to solve in iso lation from the genera l socioeconomic inequalities.J a reassessment of the resource aUocation and positive discrimination towards the deprived areas seems a timely measure.